Effect of dietary phenylalanine on growth performance and intestinal health of triploid rainbow trout (Oncorhynchus mykiss) in low fishmeal diets - Zhang, Shuze; Wang, Chang’an; Liu, Siyuan; Wang, Yaling; Lu, Shaoxia; Han, Shicheng; Jiang, Haibo; Liu, Hongbai; Yang, Yuhong (Frontiers in Nutrition, 2023)
This study aimed to investigate the effects of phenylalanine on the growth, digestive and absorptive capacity, antioxidant capacity, and intestinal health of triploid rainbow trout (Oncorhynchus mykiss) fed a low fish meal diet (15%). Five isonitrogenous and isoenergetic diets with different dietary phenylalanine levels (1.82%, 2.03%, 2.29%, 2.64%, 3.01%) were fed to triplicate groups of 20 fish (initial mean body weight of 38.65 ± 0.62 g). Weight gain rate (WGR) and specific growth rate (SGR) were significantly lower (P<0.05) in the 3.01% group. The trypsin activity in the 2.03% group was significantly higher than that in the control group (P<0.05). Serum superoxide dismutase (SOD) activity and liver peroxidase (CAT) activity both reached their maximum in the 2.03% group. Interleukin factors IL-1β and IL-6 both reached a minimum value in the 2.03% group and were significantly lower than the control group, while IL-10 reached a maximum value in the 2.03% group (P<0.05). The tight junction protein-related genes occludin, claudin-1, and ZO-1 all reached a maximum in the 2.03% treatment group and were significantly higher than the control group (P<0.05). There were also significant differences in intestinal villi length and muscle layer thickness among the groups (P<0.05). In conclusion, dietary phenylalanine effectively improved the growth, digestion and absorption capacity, antioxidant capacity, and intestinal health of O. mykiss. Using a quadratic curve model analysis based on WGR, dietary phenylalanine requirement of triploid O. mykiss fed a low fish meal diet (15%) was 2.13%.